Pengaruh pendidikan gizi terhadap pengetahuan dan sikap tentang gizi anak Sekolah Dasar - Nuryanto, Nuryanto; Pramono, Adriyan; Puruhita, Niken; Muis, Siti Fatimah (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2014)
Background: Nutrition education is one method to change the knowledge and attittude of nutrition on school children.The study aimed to see the effect of nutrition education on knowledge and attitude of nutrition among school children.Methods: The study was one group pre-post test design of a quasi experimental design. Subjects were 99 schoolchildren randomly selected through multi stage sampling method among the 4th, 5th, and 6th graders. They were givennutrition education using posters and pocket books in children meeting for three months. The data of knowledge andattitude were collected through interview using structure questionares. The differences in knowledge attitude andpractice of of nutrition among school children were tested by wilcoxon test.Results: The mean of knowledge about nutrition among school children before nutrition education is 66,45Â±9,6%increasing to 71,61Â±9,3% after nutrition education. Median of attitude before nutrition education is 70,31% increasingto 75% after nutrition education. The result showed that there was an effect of nutrition education on knowledge andattitude of school children.Conclusion: Nutrition education can improve knowledge and attitude of school children.